Incidencia de la legislación ambiental en la protección de la contaminación del río el Poste y el Derecho al Buen Vivir de la Comunidad Indígena Tsáchila. - Zambrano Romero, Jazmín Elizabeth (2022)
The Constitution of the Republic of Ecuador approved by the National Constituent Assembly in 2008, highlights in its dogmatic part in article 10 the recognition of nature as a subject of rights, following a doctrinal current known as "the new Latin American constitutionalism", which, in the opinion of Irene Zasimowicz Pinto Calaça, is "an attempt at a holistic perspective, between the environment and human beings, incorporated by the Constitutions of Ecuador and Bolivia" (Calaça, 2018, p. 159). This paradigm, developed by Zasimowicz, refers to the innovation of the Ecuadorian Constitution, on the protection of the environment with a traditional approach to the precepts of good living, recognizing the interculturality and plurinationality of indigenous people and nationalities that inhabit our territory. According to the Council of Nationalities and People of Ecuador: “In our country there are approximately 14 nationalities and 18 people, in the province of Santo Domingo; the Tsáchila community has characteristic features such as language, its own territory, customs and ancestral traditions, which identify them above the rest of the people” (FLACSO-CARE ECUADOR, 2018, p. 14) The aforementioned nationality has been affected by the growing mestizo population in its territory, as well as the advance of productive development that has generated the contamination of the El Poste river, due to the waste of agrochemical residues, solids, boiled water and pests, which affect directly the health and quality of life of the inhabitants of the Tsáchila commune in a river that is considered sacred by their culture. Legal bodies such as the Comprehensive Criminal Organic Code, sanction crimes committed against nature, while the Organic Code of Territorial Organization, Autonomy and Decentralization (COOTAD), for its part, grants responsibilities to the Decentralized Autonomous Governments regarding the protection environmental, among other laws that derive from the constitutional norm. The Ministry of the Environment issued a technical report on March 12, 2014 in relation to the contamination suffered in the El Poste, Peripa and Chigüilpe rivers in Santo Domingo, where it was possible to show "the presence of heavy metals, such as highly carcinogenic lithium and mercury; waste of lubricants, oils, etc”, making several recommendations to avoid the continuous poisoning of the rivers and the inhabitants, observations that have not been fulfilled. According to the Provincial Directorate of the Environment of Santo Domingo de los Tsáchilas, regarding the technical inspection on the case of contamination of the El Poste river, carried out in October 2016, by the Environmental Quality Unit, on the discharges of polluting water, coming from of houses and washing machines established along the banks of the El Poste river. (Technical Report No. 0821-UCA-DPASDT-2016, p. 23), it was determined that, indeed, there are two washers and lubricators established at a distance of approximately fifty meters from the shore of the El Poste River, the same as by Official Letter No. MAEUCASDT-DPASDT-2016-1887-TEMP, Official Letter No.MAE-UCASDT-DPASDT-20161894-TEMP, respectively, is made known to the legal representative of the GADP so that, based on the powers assigned as the responsible application authority, it intervenes based on current environmental regulations. In addition, it was identified that several houses established along the banks of the El Poste River were discharging wastewater directly into the aforementioned river, which, according to what is established by the COOTAD, must be controlled by the Municipal GAD, since the systems sewage and drinking water are under its jurisdiction. The Autonomous Decentralized Municipal Government of the Santo Domingo de los Tsáchilas Canton lacks its own regulations that allow, in a focused manner, to deal with the effects on the environment caused by waste, from companies such as Pronaca, as well as by the release of oils , lubricants and materials with stone remains, which have generated an environmental impact that is difficult to recover and directly affect the rights of good living, established in the Constitution of the Republic. The environmental protection regulations, established both by the Constitution of the Republic, and developed in related regulations and the competence ceded to the Provincial GAD, are insufficient to stop the growing contamination of the El Poste River, which directly affects the quality of life of the Tsachilas. The aforementioned current problem and the failure to control the full validity of environmental legislation, by public agencies, in relation to the protection of the El Poste river, causes the violation of the right to good living of the Tsáchila community, being fundamental present and activate the solution strategies that allow the authorities of the municipal and provincial Gads of the Tsáchilas, to recover the aforementioned river, through the creation of the corresponding ordinance, avoiding the violation of the right to good living, human rights and other constitutional rights . To this end, the present research work was carried out within the province of Santo Domingo de los Tsáchilas, taking into consideration the Tsáchila indigenous community. To this end, the following activities have been planned: legal and doctrinal study of the variables and analysis of cases, conducting surveys and preparing an ordinance project to prevent contamination of the El Poste river.